TINJAUAN YURIDIS TERHADAP PENEGAKAN HUKUM BERDASARKAN KETENTUAN UNDANG-UNDANG NOMOR 45 TAHUN 2009 TENTANG PERIKANAN PADA PELAKU TINDAK PIDANA PERIKANAN OLEH WARGA NEGARA ASING DI ZONA EKONOMI EKSKLUSIF INDONESIA - Martha Purba; Emilda Firdaus; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Indonesia is one country that has at the same time two geographical forms of a country characteristic, namely the archipelagic state and the mainland state. Sharing the State in the world requires the existence of legal certainty, the realization of legal certainty in the jurisdiction of a country will bring about justice, unless the law provides different regulations. Law Number 45 of 2009 concerning Fisheries is one form of concern for the state in protecting Indonesia's territorial waters in the form of all crimes and violations that occur at sea. But in reality this violation still often occurs in the Indonesian Exclusive Zone. The purpose of writing this thesis, namely: First, Juridical Review of Law Enforcement Based on the provisions of Law Number 45 Year 2009 concerning Perpetrators of Criminal Acts of Fisheries by Foreign Citizens in Indonesia's Exclusive Economic Zone, Constraints in Law Enforcement Against the Provisions of Law Number 45 of 2009 against Foreign Criminals in Fisheries in the Indonesian Exclusive Economic Zone.This type of research can be classified in this research is normative juridical and supported by empirical data which sources data from primary and secondary legal materials, and the method of data collection is done by library research. Furthermore, the data were analyzed descriptively qualitatively conducted by means of the data obtained which will be systematically compiled through a normative juridical approach then an in-depth analysis is related to the object of research and continued with conclusions.The results of the research and discussion can be concluded that the judicial review of law enforcement against fisheries criminal offenses by foreign nationals in the Indonesian Exclusive Economic Zone cannot be imposed with a substitute for criminal penalties before there is a bilateral agreement between Indonesia and the country of origin of the offender. Then the inhibiting factor in law enforcement is the factor of the law itself which causes legal uncertainty and law enforcement officials such as investigators, public prosecutors and judges who are less professional in handling cases.Keywords: Law enforcement, Illegal Fishing, Exclusive Economic Zone